Private security guards policing public space: using soft power in place of legal authority. (7th February 2021) - Kammersgaard, Tobias
ABSTRACT: Only a few studies have examined how private security guards operate in public spaces. In order to address this gap, this paper examines a public/private partnership of installing security guards on a public square in Aarhus, Denmark. This was a response to the presence of a group of homeless and marginalised alcohol and drug users. The policing of the public square was investigated through document analysis, interviews with different stakeholders and observations with a patrolling security guard. The case study illustrates that private security guards are able to exercise considerable control in public spaces, without having any legal authority over these spaces. Furthermore, by drawing on the analytical framework of governmentality studies, the case illustrates how the security guards were engaged in practices of 'soft power' in their policing of the public square. This constitutes a contribution to the growing literature that has started to survey the different powers and resources at the disposal of private security.